Synthesis of α-Hydroxy and α-Alkoxy Esters Enabled by a Visible-Light-Induced O–H Insertion Reaction of Diazo Compounds - Bai, Jinrui; Qi, Dan; Song, Zhuoheng; Li, Bin; Guo, Lin; Yang, Chao; Xia, Wujiong (Synlett, 2022)
A visible-light-induced O–H insertion reaction of diazo compounds is reported. This synthetic method, unlike conventional pathways, does not rely on transition metals, Lewis acids, or Brønsted acids; does not use any catalyst; and produces valuable α-hydroxy and α-alkoxy esters in good yields of up to 98%. The protocol exhibits a broad substrate scope and good functional-group tolerance. Notably, a gram-scale synthesis has been performed in a photochemical continuous-flow mode.
Keywords: photochemistry; diazo compounds; insertion reaction; flow reaction; hydroxy esters; alkoxy esters